Development of a triboelectric nanogenerator with enhanced electrical output performance by embedding electrically charged microparticles. (6th November 2019) - Choi, Jun Hyuk; Cha, Kyoung Je; Ra, Yoonsang; La, Moonwoo; Park, Sung Jea; Choi, Dongwhi
Abstract: A triboelectric nanogenerator (TENG) is considered a promising energy harvester, and many researchers are attempting to enhance the output performance of TENG to utilize it as a power source in practical applications. In this study, we propose a microparticle-embedded TENG (EM-TENG) that utilizes electrically pre-charged polyvinylidene fluoride (PVDF) microparticles encapsulated in polydimethylsiloxane (PDMS) as a contact layer. Electrospraying and corona charging techniques maximize the amount of electrical charges in the PVDF microparticles, while encapsulating the microparticles with PDMS prevents the escape of charges. Consequently, the amount of electrons moving between the top and bottom electrodes is increased more than that in a general TENG. The fabricated tile-sized EM-TENG generates more than 500 V with one footstep. The fabrication process of the microparticle-embedded layer is rapid, versatile, and scalable. Thus, it is a good option for increasing the output performance of TENG without limiting its size and can also be used in various applications.